HLA-B27 antigen in diagnosis of atypical seronegative inflammatory arthropathy. Issue 6 (December 1976) - Joliat, G; Ferro, A; Jeannet, M; Ott, H
Abstract : Eighteen patients with an inflammatory pauciarticular peripheral arthropathy not typical of any known entity showed an asymmetrical pattern of disease, with a predilection for the lower extremities. Destructive joint changes and deformities were absent (mean follow-up 10 years). Although spondylitis and sacroiliitis were absent on x-rays, HLA-B27 antigen was found in 8 patients (44%). This antigen and similar joint symptoms are also found in other forms of arthritis.